Localização de faltas em linhas de transmissão: desenvolvimento de novos algoritmos e implementação de sistema computacional para aplicações práticas - Eduardo Gonzaga da Silveira (2007)
Transmission line automatic fault location allows to estimate the approximate point at the line where the short-circuit occurs, using voltage and current data from one or more of its ends. The maintenance team can reach the fault local and restore the operational conditions fast and more efficiently, increasing the reliability of the power electric system and reducing the associated costs. This work presents a study about transmission line automatic fault location, with data from one or two sides, using phasor quantities. The objectives are the study of the main algorithms described in the technical literature, the proposal and development of new practical algorithms and the implementation of these algorithms in a computational system for field applications. Initially a study of transmission line models is presented, in phase and modal domains. Then, a bibliographic review is made, using the main papers related to the theme transmission line fault location. Pre-processing routines of the input data are emphasized in order to establish the necessary actions that have to be made on these input signals that lead to good final results when the location algorithms are applied in real data. The performance of some well known location algorithms is analyzed when submitted to several practical factors that can affect their results, like the employment of ground mode quantities and non balanced transmission lines faults. The objective is to analyze the influence of these factors on the final location results and to validate their application in accordance with practical cases, that is, more reliable results and smaller errors. The proposed new algorithms are then described, introducing their models and presenting the results of their applications on simulated and real transmission line fault cases. Finally the conclusions and the suggestions for future works are presented.